Before virus, after virus: A reckoning (2020)
The 2020 Lasker Awards, a celebration of one of the most prestigious international prizes given to individuals for extraordinary contributions to Basic and Clinical Medical Research, Pubic Health, and Special Achievement, was cancelled because of the COVID-19 pandemic. Typically, essays on the awardees and their scientific and medical contributions are solicited and published in Cell in collaboration with the Lasker Committee. This year, the Lasker Committee commissioned an essay to reflect on the historic contributions that scientists and physicians have made to our understanding of immunology and virology, and future directions in medical and basic research that have been highlighted by COVID-19 pandemic.